Kinerja Komoditas Elektronika Indonesia 1981-1995:Pendekatan Keunggulan Komparatif - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Electronic industry has become one of the alternatives of the high value added industrial development scheme. This paper examines the comparative advantage of Indonesian electronic commodities, utilizing of three indices of RCA (Revealed Comparative Advantage): the net export to total trade ratio, the world export share (WESif), and the export import ratio (EIR ij). In order to assess changes in comparative advantage in relation to growth of world imports, the changes of WES!, vector over the period studied is correlated with the world demand growth